Reduced expression of Na+/Ca2+ exchangers is associated with cognitive deficits seen in Alzheimer's disease model mice. (15th March 2018) - Moriguchi, Shigeki; Kita, Satomi; Fukaya, Masahiro; Osanai, Makoto; Inagaki, Ryo; Sasaki, Yuzuru; Izumi, Hisanao; Horie, Kyoji; Takeda, Junji; Saito, Takashi; Sakagami, Hiroyuki; Saido, Takaomi C.; et al.
Abstract: Na + /Ca 2+ exchangers (NCXs) are expressed primarily in the plasma membrane of most cell types, where they mediate electrogenic exchange of one Ca 2+ for three Na + ions, depending on Ca 2+ and Na + electrochemical gradients across the membrane. Three mammalian NCX isoforms (NCX1, NCX2, and NCX3) are each encoded by a distinct gene. Here, we report that NCX2 and NCX3 protein and mRNA levels are relatively reduced in hippocampal CA1 of APP23 and APP -KI mice. Likewise, NCX2 +/− or NCX3 +/− mice exhibited impaired hippocampal LTP and memory-related behaviors. Moreover, relative to controls, calcium/calmodulin-dependent protein kinase II (CaMKII) autophosphorylation significantly decreased in NCX2 +/− mouse hippocampus but increased in hippocampus of NCX3 +/− mice. NCX2 or NCX3 heterozygotes displayed impaired maintenance of hippocampal LTP, a phenotype that in NCX2 +/− mice was correlated with elevated calcineurin activity and rescued by treatment with the calcineurin (CaN) inhibitor FK506. Likewise, FK506 treatment significantly restored impaired hippocampal LTP in APP -KI mice. Moreover, Ca 2+ clearance after depolarization following high frequency stimulation was slightly delayed in hippocampal CA1 regions of NCX2 +/− mice. Electron microscopy revealed relatively decreased synaptic density in CA1 of NCX2 +/− mice, while the number of spines with perforated synapses in CA1 significantly increased in NCX3 +/− mice. We conclude that memory impairment seen in NCX2 +/− and NCX3 +/− mice reflect dysregulated hippocampal CaMKII activity, which alters dendritic spine morphology, findings with implications for memory deficits seen in Alzheimer's disease model mice. Highlights: The mRNA and protein levels of NCX2 and NCX3 in CA1 significantly reduced in APP23 and APP -KI mouse brain. NCX2 +/− or NCX3 +/− mice exhibited impaired memory-related behaviors. NCX2 +/− and NCX3 +/− mice dysregulated hippocampal CaMKII activity.